Farewell, Aylis a non-traditional novel in three works - Aĭlisli, Akram (Central Asian Literatures in Translation, 2018)
The three novellas of Farewell, Aylis explore a society in transition: a traveler is suspected of defecting to America, an actor undergoes an existential crisis, and the inhabitants of a corrupt country scheme to survive. A new essay by the author reflects on his experience as a prisoner of conscience in today's Azerbaijan